Chemical Signals from Avocado Surface Wax Trigger Germination and Appressorium Formation in Colletotrichum gloeosporioides. - Podila, G. K. (1993)
The surface wax of the host, avocado (Persea americana) fruit, induced germination and appressorium formation in the spores of Colletotrichum gloeosporioides. Waxes from nonhost plants did not induce appressorium formation in this fungus, and avocado wax did not induce appressorium formation in most Colletotrichum species that infect other hosts. Bioassays of the thin-layer chromatographic fractions of the avocado wax showed that the fatty alcohol fraction was the main appressorium-inducing component. Testing of authentic n-C8 to n-C32 fatty alcohols revealed that C24 and longer-chain alcohols induced appressorium formation. Gas-liquid chromatography/mass spectrometry analysis of free fatty alcohols revealed that avocado wax contains a high content of very long chains. Waxes from nonhost plants containing an even higher content of the very long-chain alcohols did not induce appressorium formation. Waxes from nonhost plants strongly inhibited appressorium induction by avocado wax. Thus, a favorable balance between appressorium-inducing very long-chain fatty alcohols and the absence of inhibitors allows the fungus to use the host surface wax to trigger germination and differentiation of infection structures in the pathogen.